China-India special representatives talks : moving beyond the boundary dispute? - Jabin T. Jacob (2012)
The 15th round of talks between the Chinese and Indian Special Representatives on the boundary dispute suggests a desire to minimise the role of the dispute in bilateral ties and to move discussions to include regional and global issues.